1991
DOI: 10.1017/s0954579400007562
|View full text |Cite
|
Sign up to set email alerts
|

Quality of attachment and home environments in children prenatally exposed to PCP and cocaine

Abstract: Quality of attachment, disorganization in attachment, and the contribution of caregiver interactions in the home were investigated for infants prenatally exposed to PCP and cocaine and their caregivers. The drug-exposed infants were compared with infants of similar ethnicity, socioeconomic status (SES), and living in the same geographical area of the city with non-substance-abusing mothers. The majority of drug-exposed infants were insecurely attached to their caregivers and did not differ in the percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0
6

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 42 publications
(29 reference statements)
4
87
0
6
Order By: Relevance
“…Observational studies have shown that, in interaction with their infants, women with substance abuse issues show a lack of sensitivity and responsiveness to emotional cues and heightened physical activity, provocation, and intrusiveness (Hans, Bernstein, & Henson, 1999;Rodning, Beckwith, & Howard, 1991). Research on infants of methodone-using mothers has shown that they demonstrate higher levels of disorganized attachment than infants of nondrug-using mothers (Goodman, Hans, & Cox, 1999;Rodning et al, 1991). Also, mothers with substance use issues report a lack of understanding of child development, ambivalent feelings about their children, and lower capacity to reflect upon their children's experience (Mayes & Truman, 2002).…”
Section: Parenting In the Context Of Substance Abusementioning
confidence: 99%
“…Observational studies have shown that, in interaction with their infants, women with substance abuse issues show a lack of sensitivity and responsiveness to emotional cues and heightened physical activity, provocation, and intrusiveness (Hans, Bernstein, & Henson, 1999;Rodning, Beckwith, & Howard, 1991). Research on infants of methodone-using mothers has shown that they demonstrate higher levels of disorganized attachment than infants of nondrug-using mothers (Goodman, Hans, & Cox, 1999;Rodning et al, 1991). Also, mothers with substance use issues report a lack of understanding of child development, ambivalent feelings about their children, and lower capacity to reflect upon their children's experience (Mayes & Truman, 2002).…”
Section: Parenting In the Context Of Substance Abusementioning
confidence: 99%
“…Depressed mothers have tended to be rated as hostile and intrusive, withdrawn, showing negative affect, or less sensitively attuned, and infant distress and avoidance have been common~e.g., Cohn, Campbell, Matias, & Hopkins, 1990;Cohn, Matias, Tronick, Connell, & Lyons-Ruth, 1986;Field, Healy, Goldstein, & Guthertz, 1990;Field, Healy, Goldstein, Perry, Bendell, Schanberg, Zimmerman, & Kuhn, 1988;Field, Sandberg, Garcia, Vega-Lahr, Goldstein, & Gay, 1985;Murray, Fiori-Cowley, Hooper, & Cooper, 1996!. Other studies have concerned early mother-child relations and0or attachment in the context of maternal anxiety disorder~Manassis, Bradley, Goldberg, Hood, & Swinson, 1994!, alcoholism and drug abuse~O 'Connor, Sigman, & Brill, 1987;Rodning, Beckwith, & Howard, 1991!, eating disorders Stein, Woolley, Cooper, & Fairburn, 1994McPherson, 1999!, andpsychotic depression andmania~Hipwell, Goossens, Melhuish, &Kumar, 2000!.…”
Section: According To the Diagnostic And Statistical Manual Of The Ammentioning
confidence: 99%
“…High levels of attachment disorganization/ disorientation in infancy have been related to parental experiences of unresolved mourning (Main & Hesse, 1990) and to maternal histories of loss due to divorce, separation, and death (Lyons-Ruth, Repacholi, McLeod, & Silva, 1991). Attachment disorganization/ disorientation (including the unclassifiable A/C pattern) has been related to infant histories of maltreatment (Carlson, Cicchetti, Barnett, & Braunwald, 1989), hostile and intrusive caregiving (Lyons-Ruth et al, 1991), maternal depression (Radke-Yarrow, Cummings, Kuczynski, & Chapman, 1985), and prenatal alcohol (O'Connor, Sigman, & Brill, 1987) and drug exposure (Rodning, Beckwith, & Howard, 1991). In studies of prenatal alcohol and drug exposure, researchers suggest that caregiver relationships were compromised by the ongoing drug or alcohol use and patterns of use interfering with parenting interaction and the parenting role.…”
Section: Introductionmentioning
confidence: 99%